EFFECTS OF DIFFERENT COOLING RATES USING PROGRAMMABLE FREEZER ON POST THAW SURVIVAL OF DOG SPERMATOZOA - UMAMAGESWARl, J; JOSEPH, CECILIA; KULASEKAR, K; KALATHARAN, J; SRIDEVl, P (The Indian Journal of Animal Reproduction, 2023)
Semen collected by digital manipulation from eighteen healthy and sexually matured dogs of three differentbreeds viz., Labrador Retriever (n=B), German Shepherd (n= 6), Boxer ( n = 4) aged between 2 to 6 years wasdiluted with Tris - fructose - citric acid extender containing 8% glycerol and 20% egg yolk at the rate of 1 :2 andpacked in French mini straws. They were frozen at the three different cooling rates of programmable freezing viz.Slow (R1), Medium (R2) and Fast (R3) at -1p C/min for 30min, -Sp C/min for 10min and -10p C/min for 7minrespectively. The mean percentages of post-thaw motility, live spermatozoa, normal spermatozoa, acrosomalintegrity and plasma membrane integrity were significantly higher (P.::. 0.05) following slow cooling rate (R 1) thanother rates of programmable freezing. Hence, slow cooling rate (R1) of programmable freezing is suggested to beoptimum for freezing dog semen.
Keywords: Spermatozoa; Acrosomal integrity; Programmable freezing